2019
DOI: 10.1024/1016-264x/a000262
|View full text |Cite
|
Sign up to set email alerts
|

Validierung des QbMini Tests zur Diagnose der Aufmerksamkeitsdefizit-/Hyperaktivitätsstörung (ADHS) bei fünfjährigen Kindern

Abstract: Zusammenfassung. Fragestellung: ADHS tritt bei 2 %-8 % aller Vorschüler auf. Zur Diagnose von ADHS im Vorschulalter gibt es derzeit nur wenige Verfahren. Ziel dieser Studie war die Validierung des psychometrischen Verfahrens QbMini Test für das Vorschulalter. Dieser PC-gestützte Test erfasst Aufmerksamkeit und Impulsivität anhand eines Daueraufmerksamkeitstests, während die Hyperaktivitätsmessung über eine Infrarotkamera erfolgt. Methodik: Der QbMini Test wurde mit 95 5-jährigen Kindern mit und ohne ADHS durch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…The factor analysis revealed that the different variables computed when children perform the QbMini task while filmed by an infrared camera mapped onto the three symptom domains. This three-factor model is in line with analyses performed on the already validated QbTests (Reh et al, 2015;Ulberstad, 2012aUlberstad, , 2012b as well as the QbMini itself (Zaplana Labarga et al, 2019). An earlier factor model of the QbMini (Lamm, 2013) consists of only two factors (inattention and hyperactivity/impulsivity), in line with others performed on the QbTest and the conception of the FBB-ADHS-V, in which hyperactivity and impulsivity are merged into one scale as well.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The factor analysis revealed that the different variables computed when children perform the QbMini task while filmed by an infrared camera mapped onto the three symptom domains. This three-factor model is in line with analyses performed on the already validated QbTests (Reh et al, 2015;Ulberstad, 2012aUlberstad, , 2012b as well as the QbMini itself (Zaplana Labarga et al, 2019). An earlier factor model of the QbMini (Lamm, 2013) consists of only two factors (inattention and hyperactivity/impulsivity), in line with others performed on the QbTest and the conception of the FBB-ADHS-V, in which hyperactivity and impulsivity are merged into one scale as well.…”
Section: Discussionsupporting
confidence: 84%
“…First, the test must be able to differentiate between the three main symptoms of ADHD (construct validity). Comparing to the previous results of Zaplana Labarga et al (2019), we expected that the variables of the QbMini can be classified into three factors for hyperactivity, inattention, and impulsivity. In the second step, we wanted to examine the diagnostic ability of the QbMini.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…After this initial validation, very few studies have replicated these findings to further explore the structure of the QbTest in pediatric populations (Table 1). Reh et al (2015) also found three factors in explorative factor analysis (EFA), and so did Labarga et al (2019) in a principal component analysis (PCA) study, while Hirsch and Christiansen (2017) and Hamadache et al (2021) reported only two factors. However, Hirsch and Christiansen (2017) found three factors in separate confirmatory factor analysis (CFA).…”
Section: Introductionmentioning
confidence: 99%